Analysis and Design Ecommerce with User Centered Design (UCD) Method at PT. Multi Prima Mandiri Sukses - Singgih Tanu Putra; Edy Edy (Tech-E, 2020)
The development of technology moves so rapidly beyond human expectations in general, all eyes and minds are shocked by the sophistication of a technology that is packaged to represent various systems in the world, as well as the business world which is touched by technological developments and changes the way of doing business from the old model to be more sophisticated and efficient. PT. Multi Prima Mandiri Sukses is a company that sells laserjet toner ink and various laserjet printer rentals for office needs. The problem that occurs is in the sales department that so far sales are still carried out conventionally by ordering by telephone and sales records are still in the form of physical data where sales reach is not wide and sales data are easily lost. To overcome this problem, an online sales platform was built in the form of e-commerce with the UML (Unified Modeling Language) approach and with the design of the UCD (User Centered Design) method, the programming language used was PHP with MySQL database. The results of this research are in the form of an available online sales system which includes purchases and sales reports with a user center as a reference for developing an e-commerce sales system.